2005
DOI: 10.1086/497331
|View full text |Cite
|
Sign up to set email alerts
|

The Gemini Deep Deep Survey. VII. The Redshift Evolution of the Mass‐Metallicity Relation

Abstract: We have investigated the mass-metallicity (M-Z ) relation using galaxies at 0:4 < z < 1:0 from the Gemini Deep Deep Survey (GDDS) and Canada-France Redshift Survey (CFRS). Deep K-and z 0 -band photometry allowed us to measure stellar masses for 69 galaxies. From a subsample of 56 galaxies, for which metallicity of the interstellar medium is also measured, we identified a strong correlation between mass and metallicity for the first time in the distant universe. This was possible because of the larger baseline … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

57
659
10
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 493 publications
(727 citation statements)
references
References 83 publications
(172 reference statements)
57
659
10
1
Order By: Relevance
“…The correlations between metallicity and other fundamental galaxy properties such as stellar mass, luminosity, and star formation rate are crucial to understanding galaxy populations at both low and high redshifts (e.g., Tremonti et al 2004;Savaglio et al 2005;Maiolino et al 2008;Mannucci et al 2010), including DLA galaxies (e.g., Ledoux et al 2006;Fynbo et al 2008;Pontzen et al 2008;Prochaska, Hennawi, & Herbert-Fort 2008;Krogager et al 2012;Møller et al 2013). Møller et al (2013) analyze the redshift evolution of the mass-metallicity relation in a sample of 110 DLAs and report a formula (Equation 6) for estimating stellar mass given metallicity and redshift.…”
Section: Mass-metallicity Relationmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlations between metallicity and other fundamental galaxy properties such as stellar mass, luminosity, and star formation rate are crucial to understanding galaxy populations at both low and high redshifts (e.g., Tremonti et al 2004;Savaglio et al 2005;Maiolino et al 2008;Mannucci et al 2010), including DLA galaxies (e.g., Ledoux et al 2006;Fynbo et al 2008;Pontzen et al 2008;Prochaska, Hennawi, & Herbert-Fort 2008;Krogager et al 2012;Møller et al 2013). Møller et al (2013) analyze the redshift evolution of the mass-metallicity relation in a sample of 110 DLAs and report a formula (Equation 6) for estimating stellar mass given metallicity and redshift.…”
Section: Mass-metallicity Relationmentioning
confidence: 99%
“…One is the evolution of metallicity as a function of redshift; metallicity gradually increases with decreasing redshift (Prochaska et al 2003;Kulkarni et al 2005;Rafelski et al 2012Rafelski et al , 2014. The second one is the correlation between the metallicity and kinematics (Wolfe & Prochaska 1998;Ledoux et al 2006;Prochaska, Hennawi, & Herbert-Fort 2008;Neeleman et al 2013), which is largely due to the underlying massmetallicity relation that has been well-established in galaxies at high and low redshifts (Tremonti et al 2004;Savaglio et al 2005;Erb et al 2006;Maiolino et al 2008;Møller et al 2013;Neeleman et al 2013). The correlations between metallicity and other fundamental parameters such as stellar mass and star formation rate are key to understanding various galaxy populations (Calura et al 2009;Mannucci et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This mass-metallicity relation (MZR) has also been investigated at higher z but with an apparent offset towards lower metallicities with respect to the local MZR (e.g. Savaglio et al 2005;Erb et al 2006;Maiolino et al 2008). However, a comparison between observational works at different redshifts is not straightforward because of selection biases, aperture effects and the use of different metallicity indicators (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The heavy element content of star-forming galaxies is characterized by a strong relation between the stellar mass and average gas-phase oxygen abundance (Lequeux et al 1979;Tremonti et al 2004). This so-called mass-metallicity relation (MZR) extends to low stellar mass galaxies (∼ 10 7 M⊙ Lee et al 2006;Zahid et al 2012a;Berg et al 2012) and is observed at intermediate (Savaglio et al 2005;Cowie & Barger 2008;Zahid et al 2011;Moustakas et al 2011;Zahid et al 2013a) and high redshifts (Erb et al 2006;Mannucci et al 2009;Laskar et al 2011). The metallicity at all stellar masses increases with time and the high mass end of the relation flattens at late times as galaxies enrich to an empirical upper limit in the gas-phase abundance (Zahid et al 2013a).…”
Section: Introductionmentioning
confidence: 90%